2021
DOI: 10.1021/acsmedchemlett.0c00636
|View full text |Cite
|
Sign up to set email alerts
|

1,5-Disubstituted 1,2,3-Triazoles as Amide Bond Isosteres Yield Novel Tumor-Targeting Minigastrin Analogs

Abstract: 1,5-disubstituted 1,2,3-triazoles (1,5-Tz) are considered bioisosteres of cis-amide bonds. However, their use for enhancing the pharmacological properties of peptides or proteins is not yet well established. Aiming to illustrate their utility, we chose the peptide conjugate [Nle 15 ]MG11 (DOTA-DGlu-Ala-Tyr-Gly-Trp-Nle-Asp-Phe-NH2) as a model compound since it is known that the cholecystokinin-2 receptor (CCK2R) is able to accommodate turn conformations. Analogs of [Nle 15 ]MG11 incorporating 1,5-Tz in the back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Stability studies in vitro using human blood plasma did not show any metabolites for radiolabeled PP-F11N and NMGs after 24 h of incubation ( Figure 3 ), likely due to the stabilizing effect of the N-terminal hexaglutamate moiety in vitro [ 28 ]. This is in contrast to previously evaluated triazole-bearing analogs of minigastrin lacking the N-terminal extension [ 16 , 17 , 27 ]. To evaluate whether the amide-to-triazole substitutions stabilize the analogs of PP-F11N in vivo, we investigated samples of blood and urine of mice at 10 min p.i.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Stability studies in vitro using human blood plasma did not show any metabolites for radiolabeled PP-F11N and NMGs after 24 h of incubation ( Figure 3 ), likely due to the stabilizing effect of the N-terminal hexaglutamate moiety in vitro [ 28 ]. This is in contrast to previously evaluated triazole-bearing analogs of minigastrin lacking the N-terminal extension [ 16 , 17 , 27 ]. To evaluate whether the amide-to-triazole substitutions stabilize the analogs of PP-F11N in vivo, we investigated samples of blood and urine of mice at 10 min p.i.…”
Section: Discussionmentioning
confidence: 74%
“…A general requirement for applications of CCK2R-targeting peptides in nuclear medicine is a high tumor uptake with minimal distribution to healthy organs and tissues. We have recently reported that substitutions of single or multiple amide bonds with metabolically stable 1,4 or 1,5-disubstituted 1,2,3-triazoles improved the tumor-targeting characteristics of the truncated minigastrin analog [Nle 15 ]MG11 [ 16 , 17 , 27 ]. The triazole-containing analogs of [Nle 15 ]MG11 exhibited higher affinities toward the CCK2R and increased stability against enzymatic degradation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it is noteworthy that the use of a protective group using an ester is indispensable due to the incompatibility of the ruthenium-catalyzed azide-alkyne cycloaddition (RuAAC) approach with carboxylic acids. Following the same strategy, Stålsmeden [81] and Grob [82], and their respective collaborators, developed a series of novel peptide drugs that have also been biologically tested. In the first case, it has been realized that the RuAAC synthesis of chiral 1,5-disubstituted 1,2,3-triazoles aiming to obtain foldamers useful in pharmaceutics and biotechnology.…”
Section: Synthesis Of 15-disubstituted 123-triazolesmentioning
confidence: 99%
“…Ru-catalyzed synthesis of 1,5-disubstitute 1,2,3-triazoles as bioisosteres of the amide bond. Furthermore, Grob[82] et al took advantage of the RuAAC synthesis of 1,2,3triazoles for realizing a series of novel minigastrin analogs successfully tested toward cholecystokinin-2 receptor (CCK2R). Scheme 31 only regards the reaction step where the triazolyl moiety is formed starting from an α-azido Bn-protected ester 98 and a Fmocprotected amino-propargyl derivative 99.…”
mentioning
confidence: 99%
“…In nearly two decades following the latter discovery, numerous medicinal chemistry applications of this chemotype have been found. The most recently identified, useful bioactivities include inhibition of RhoGTPases for the treatment of hyperprofilerative and neoplastic diseases, inhibition of mitochondrial permeability transition pore for the treatment of various diseases associated with mitochondrial dysfunction, and antitumor activity of minigastrin peptide analogues . In the majority of cases reported in the literature, 1,5-disubstituted 1,2,3-triazoles have been assembled using metal-catalyzed methods.…”
mentioning
confidence: 99%